Thalamic Deep Brain Stimulation for tremor: The critical role of intraoperative testing. (April 2020) - Mahajan, Abhimanyu; Bader, Alexander; Wang, Lily L.; Rekhtman, Aleksander; Espay, Alberto J.; Dwivedi, Alok K.; Sturchio, Andrea; Marsili, Luca; Duker, Andrew P.; Krishna, Vibhor; Mandybur, George T.; Merola, Aristide
Abstract: Introduction: Optimal placement of Deep Brain Stimulation (DBS) lead is critical to ensure an adequate therapeutic benefit and minimize stimulation-induced side effects. Methods: We reviewed data from 2004 to 2018 of all cases of essential tremor treated with thalamic DBS at the University of Cincinnati. All procedures were performed with the patient awake. Change in parallel trajectory was classified as major repositioning, whereas a change in depth of electrode classified as minor repositioning. The following data were compared between groups (no vs. minor vs. major repositioning): age at surgery, sex, AC-PC length, third ventricle width, cerebral atrophy, small vessel disease burden, and intraoperative tremor control. Univariate and multivariate analyses were conducted to identify factors associated with intraoperative repositioning. Results: Of the 127 encounters with essential tremor, 71 required repositioning (33 major and 38 minor). Comparing procedures with major, minor, and no repositioning, mean number of changes per procedure (4 vs. 1.2 vs 0; p < 0.001) and AC-PC length (26 vs. 27 vs. 27.2 mm; p = 0.021) differed between the three groups. Older age at surgery (OR 1.04, p = 0.042), left side (OR 2.56, p = 0.04) and decrease in AC-PC length (OR 1.33, p = 0.026) were associated with greater odds of any (minor or major) repositioning. A decrease in AC-PC length was associated with greater odds of major repositioning (OR 1.37, p = 0.009). Conclusion: Intraoperative functional testing may be critical to ensure the accuracy of thalamic DBS targeting based on neuroimaging data, particularly in patients with reduced AC-PC length. Highlights: We reviewed 127 VIM DBS procedures for essential tremor over 14 years. Intraoperative testing led to requirement of an additional trace in 26% of the cases. AC-PC length was associated with greater odds of additional tracing.